PENERAPAN KLAUSULA EKSENORASI PADA PERJANJIAN FORMULIR PEMBUKAAN REKENING NASABAH PADA BANK KONVENSIONAL DI BANDAR LAMPUNG - Chairy Naima Amalia (Indonesia Private Law Review, 2020)
The application of the deposit clause in banking agreements such as account opening forms and credit distribution forms, causes the position of consumers in this case the bank's creditors' customers become weaker. The problem will be discussed in this study are how the application of the exploration clause in conventional banks? What are the legal arrangements regarding the exoneration clause? The research method used is an normative legal approach. Research shows that the agreement for opening a customer account is based on a sample of 3 conventional banks in Lampung Province that the agreement fulfills the elements of an agreement in accordance with the Financial Services Authority Regulation (POJK) and this agreement is a form of an exoneration agreement. This can be seen from the form or model of an agreement for opening a savings account at a bank that has generally been made in the form of a standard form containing various things that must be filled out by prospective creditors. The fact is that the form of legal protection for depositors' creditors against the exoneration clause in the form of opening a savings account at a commercial bank is regulated in the Civil Code, the UUPK and POJK.